Perspective and potential of CO2: A focus on potentials for renewable energy conversion in the Mediterranean basin. (May 2016) - Boubaker, Karem; Colantoni, Andrea; Marucci, Alvaro; Longo, Leonardo; Gambella, Filippo; Cividino, Sirio; Gallucci, Francesco; Monarca, Danilo; Cecchini, Massimo
Abstract: Figures commonly quoted on the soon shortage of generating energy from fossil sources which may give the impression that it will be possible to switch to renewable energies conversion as foundations for the future of industrial instances in the Mediterranean basin. In this study, CO2 energy potential and perspectives in the Mediterranean basin have been investigated in terms of efficiency, feasibility, geographical patterns and savings. Two conjoint mathematical protocols have been carried out in order to yield a simplified extracted scheme for prototype CO2 trapping/storage plants. Graphical abstract: Highlights: Original investigation in terms of CO2 cutisation and storage. Gathering conjoint classical and scientific analyses on energy conversion and management. Presenting an original optimizing scheme for implementing CO2 plants in the Mediterranean basin. Outlining adequacy of the process and the theory under a broad range of governing parameters and application levels.